Memperkenalkan Sejarah Pahlawan Nasional K.H. Samanhudi bagi Peserta Didik MI/SD di Indonesia - Lutfiah Hamidah; Anis Fuadah Z (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
The enthusiasm of Kyai Haji Samanhudi in advancing the indigenous merchant class against Chinese merchants resulted in the idea of establishing Sarekat Dagang Islam. Sarekat Dagang Islam was originally a group of batik traders whose aim was to improve the lives of its members. However, over time, membership has grown rapidly, starting from the groups of farmers, laborers and other traders. To expand its reach, this organization changed its name to Sarekat Islam and succeeded in penetrating various fields such as economics, politics, religion and society. The organization, which was founded in 1912, will later become the embryo and spirit of unity for the success of the economic movement in Indonesia during the movement era.This study describes (1) the biography of the hero Kyai Haji Samanhudi, (2) the values of K.H. Samanhudi in establishing and running Sarekat Dagang Islam to Sarekat Islam (3) the influence of K.H. Samanhudi towards society in the political, economic, religious and social fields (4) the heroic values of K.H. Samanhudi towards students in MI / SD.